M-Government: Measuring the Factors that influence Mobile Government Services Acceptance among Bahraini Youth - Ali, Hayat; Sahwan, Reem; Shamsaldeen, Zainab; Rajulla, Nafeesa (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
In recent years, the advancement of Information and Communication Technologies (ICTs) and particularly the rapid changes in mobile technologies have led to the development of new applications. Many governments worldwide have started moving towards Mobile Government (M-Government) as M-government can be a powerful component of the e-government that could facilitate more and better services to the citizens. For a better application of these services, it is important to investigate the factors that influence the intention to use M-government services. Therefore, this study is to investigate the factors that influence the intention to use M-Government services among Bahraini Youth. The theoretical model that was developed by [1] was employed for this purpose. The model is tested through a survey administered to Bahraini Youth. Results suggested Perceived Trust in Technology, Perceived Service Quality, and Perceived Compatibility affect Youth’s intention to use M-services. The results also revealed that Ease of Use and Usefulness are antecedents to attitude toward using M-services. This research provides mobile service providers in Kingdom of Bahrain with a practical and communicable checklist of contextual and conditional factors, which are seamlessly integrated, and cover the end users (Youth) perspectives which should be considered as the cornerstone for any M-Government project.